Fadiga perioperatória, características psicoemocionais e perfil bioquímico de mulheres com câncer de mama submetidas a mastectomia - Ribeiro, Milainy Barbosa (2017)
Breast cancer is one of the most frequent in Brazil and worldwide. Mastectomy is commonly employed for its treatment and has fatigue as one of the most prevalent postoperative side effects. Factors related to the development of fatigue have been investigated, with emphasis on the identification of biochemical factors and psychoemotional symptoms with a view to directing the prevention or intervention of fatigue. Current research involving cancer and fatigue evaluates several biochemical parameters, however they are limited in the representation of patients submitted to surgery. OBJECTIVE: To evaluate the correlation between fatigue and psychoemotional characteristics (anxiety, depression and stress) and biochemical parameters (erythrocyte count, hematocrit, hemoglobin, leukocyte, segmented, platelet, insulin, fibrinogen, dehydroepiandrosterone sulfate - DHEA- C-reactive enzyme - ultra-sensitive CRP, interleukin 6, tumor necrosis factor-TNF-α, serotonin, plasma cortisol, high density lipoprotein - HDL and total cholesterol) in women with breast cancer undergoing mastectomy. METHOD: This is a longitudinal, prospective study in which women with breast cancer undergoing surgical treatment were included. The patients were evaluated in the pre- and postoperative period through the Piper Fatigue Scale - revised, Hospital Anxiety and Depression Scale - HADS, Peceased Stress Scale and blood samples for the analysis of biochemical factors. Bivariate and multivariate analyzes were used to verify the relationship between postoperative fatigue and sociodemographic, clinical variables and expression of biochemical parameters. RESULTS: The study included 40 patients (mean age: 53.1 ± 14.3 years, 62.5% brown or black, schooling: 8.0 ± 4.4 years, 67.5% postmenopausal). The predominant surgical procedure was radical mastectomy. The fatigue experienced by the patients in the postoperative period was moderate and significantly higher postoperatively than in the preoperative period (p <0.001). Mean anxiety score did not change significantly, but depression (4.8 versus 6.7, p = 0.016) and stress (23.5 vs 28.2, p <0.001) increased significantly from preoperative to the postoperative period. There was a significant increase in the postoperative period of interleukin-6 (p <0.001), plasma cortisol (p = 0.001), insulin (p = 0.018), fibrinogen (p <0.001), C- -α (p <0.001). The multivariate analysis allowed us to observe depression and TNF-α as variables with a significant positive correlation with postoperative fatigue. CONCLUSION: Fatigue positively and significantly correlated with elevated levels of TNF-α and depressive symptoms. Research is needed to adopt intervention measures to control TNF-α and the use of coping with depressive symptoms